Cross-cultural psychometric assessment of an appetite questionnaire for patients with cancer - Bernardes Spexoto, Maria Claudia [UNESP]; Serrano, Sergio Vicente; Halliday, Vanessa; Maroco, João; Wilcock, Andrew; Campos, Juliana Alvares Duarte Bonini [UNESP] (FapUNIFESP (SciELO), 2018)
Objective: To evaluate the psychometric properties, along with cross-cultural invariance analysis, of the Cancer Appetite and Symptom Questionnaire (CASQ). Method: Data from 555 United Kingdom (UK) cancer patients were used to evaluate the psychometric properties of the CASQ. Construct validity was assessed through factorial and convergent validity. We conducted a confirmatory factor analysis using as indices the chi-square ratio by degrees of freedom (χ2/df), the comparative fit index (CFI), the goodness of fit index (GFI), and the root mean square error of approximation (RMSEA). Convergent validity was estimated by the items’ average variance extracted (AVE). Reliability was estimated by composite reliability and internal consistency. Factorial invariance analysis of the CASQ was evaluated by multigroup analysis (∆χ2) using the UK and Brazilian samples. Results: All items showed adequate psychometric sensitivity in the UK sample. One item was removed and four correlations were included between errors with an appropriate fit of the model (χ2/df = 2.674, CFI = 0.966, GFI = 0.964, RMSEA = 0.055). The reliability of the CASQ was adequate and the convergent validity was low. The factorial structure of the CASQ differed across countries, and a lack of measurement invariance for the two countries was observed (λ: ∆χ2 = 64.008, p < 0.001; i: ∆χ2 = 3515.047, p < 0.001; Res: ∆χ2 = 4452.504, p < 0.001). Conclusion: The CASQ showed adequate psychometric properties in the UK sample. The ability to estimate loss of appetite and the presence of symptoms was different between UK and Brazilian patients.
Avaliação psicométrica transcultural de um questionário de apetite para pacientes com câncer
Keywords: Appetite; Cancer; Cross-cultural study; Symptom